2015
DOI: 10.1158/1535-7163.mct-14-0892
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K Pathway Reduces Invasiveness and Epithelial-to-Mesenchymal Transition in Squamous Lung Cancer Cell Lines Harboring PIK3CA Gene Alterations

Abstract: A prominent role in the pathogenesis of squamous cell carcinoma of the lung (SQCLC) has been attributed to the aberrant activation of the PI3K signaling pathway, due to amplification or mutations of the p110a subunit of class I phosphatidylinositol 3-kinase (PIK3CA) gene. The aim of our study was to determine whether different genetic alterations of PIK3CA affect the biologic properties of SQCLC and to evaluate the response to specific targeting agents in vitro and in vivo. The effects of NVP-BEZ235, NVP-BKM12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
0
29
0
1
Order By: Relevance
“…Several lines of evidence indicate that the phosphatidylinositol 3-kinase (PI3K)/Akt pathway plays a key role in cancer stem cell biology (24), and some studies suggest that the PI3K/Akt pathway may regulated RhoA activity in various solid tumors (25, 26). We thus examined this signaling pathway in diffuse gastric cancer spheroid cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence indicate that the phosphatidylinositol 3-kinase (PI3K)/Akt pathway plays a key role in cancer stem cell biology (24), and some studies suggest that the PI3K/Akt pathway may regulated RhoA activity in various solid tumors (25, 26). We thus examined this signaling pathway in diffuse gastric cancer spheroid cells.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that co-treatment of an MEK inhibitor and BKM120 in NSCLC cell lines with KRAS mutations significantly inhibited the growth of tumors both in vitro and in vivo (24). In the clinic, drug decisions are usually based on a genetic mutation test to govern the use of drugs common in personalized therapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 200 cells were seeded and after 1–3 days the spheroids were formed and treated with drugs or vehicle for 96 hours. The effects of the drugs were evaluated in terms of volume changes as previously described [16].…”
Section: Methodsmentioning
confidence: 99%